ВПЛИВ НАГРІВУ ПОСТІЙНИХ МАГНІТІВ НА ХАРАКТЕРИСТИКИ ПОТУЖНИХ СИНХРОННИХ МАГНІТОЕЛЕКТРИЧНИХ ДВИГУНІВ - Васьковський, Ю.М.; Нестеренко, Д.С. (Інститут електродинаміки НАН України, Київ, 2025)
This study examines a 140 kW traction permanent magnet synchronous motor (PMSM), designed for shunting locomotives and traction metro locomotives. The influence of active zone heating on the operational characteristics of the motor, with a particular focus on permanent magnets, is analysed. During PMSM operation, PM heating leads to reduction of its magnetic properties and a corresponding power loss, affecting the motor’s reliable performance. Therefore, a reliable analysis of PMSM characteristic changes caused by PM heating is essential. The purpose of this work is to develop a complex multiphysics mathematical model of the PMSM and assess the impact of PM heating on motor characteristics. The objective is achieved through the development of a complex multiphysics mathematical model that accounts the mutual influence of electromagnetic, thermal, and ventilation processes in PMSM ensuring high modelling accuracy. Mathematical modelling has provided crucial insights into the significant impact of PM heating on PMSM power reduction. It has been established that for every 1°C increase in PM temperature, the PMSM loss about 0.12% of its power in average. The practical significance lies in substantiated technical proposals for increasing the level of PM temperature stabilization, which contributes to the PMSM characteristics stabilization. References 18, tables 2, figures 3.